PENINGKATAN KOMPETENSI GURU RA MARIA ULFAH TERHADAP KETERAMPILAN MEMBACA BAHASA ARAB MELALUI METODE COOPERATIVE SCRIFT - Jubaidah, Siti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2023)
Abstract This community engagement activity is themed “ Enhancement of Competence of R. A Maria Ulfah’ Teachers in Arabic Language Learning through the Cooperative Scrift Method”. This activity aims to: 1) enhance the competence of R.A Maria Ulfah’s teacheres in Arabic language reading skills through effective and engaging teaching methods; 2) provide training in creating PowerPoint media for Arabic language reading materials based on Artificial Intelligence (AI).Considering and understanding the importance of teacher competence in reading Arabic language and the skill of using interactive media for teachers in the teaching process, a solution needs to be found for this issue. One of the solutions that can be implemented to address the aforementioned problem is by providing Arabic language reading training for teachers using an effective, interactive, and engaging teaching method based on 21st-century skills.To achieve these objectives, this activity is designed as an educational training, encompassing seminar presentations, workshops with interactive and enjoyable dialogues. The target audience for this community engagement activity is the R.A. Maria Ulfah teachers. The activity is structured in the form of training and education and will be carried out by a team of faculty members and students from the Arabic Language Education program, Faculty of Language and Arts, as well as faculty members from the Public Relations program, Faculty of Social Sciences, Universitas Negeri Jakarta, for the R.A. Maria Ulfah teachers. Abstrak Kegiatan pengabdian kepada masyarakat ini bertema: “Peningkatan Kompetensi Guru R.A Maria Ulfah Terhadap Pembelajaran Bahasa Arab Melalui Metode Cooperatif Scrift